A facile co-precipitation synthesis of robust FeCo phosphate electrocatalysts for efficient oxygen evolution. (20th February 2018) - Wang, Zhaojie; Liu, Ming; Du, Jiao; Lin, Yan; Wei, Shuxian; Lu, Xiaoqing; Zhang, Jun
Abstract: The oxygen evolution reaction (OER) involved in water splitting is considered as the rate-determining step due to the requirement of a relatively high overpotential for non-noble-metal electroctalysts. Chemical composition engineering is one of the most valid approaches to regulate the active sites for improved activity. Here we developed new robust OER electrocatalysts of FeCo phosphate (FCP) composites by a simple and low-cost co-precipitation method. The electrocatalytic activity depends intensely on the composition tuning by the dosage of Fe and Co precursor and the optimized catalyst requires overpotentials of only 273 and 298 mV to drive current densities of 10 and 50 mA cm −2 in 1 M KOH, respectively. It shows a low Tafel slope of 35.9 mV dec −1 . Meanwhile, the faradaic yield was determined to be ∼96% together with excellent stability for long-term OER. Both the collective effects of phosphate anion features and the regulation of cations were discussed for the enhancement in OER electrocatalysis. The strategy proposed here provides a new insight for in-depth understanding and designing of high-performance OER electrocatalysts. Graphical abstract: Highlights: FeCo phosphate with different Fe/Co ratio was co-precipitated simply for OER. Co-precipitation provided the morphology and composition evolution by Fe precursor. The optimum electrocatalysts exhibited a small overpotential of 273 mV@10 mA cm −2 . Both the phosphate anion and cations regulation contributed for the enhancement.